Mammals of the Tandilia Mountain system, current species inhabiting Pampean highland grasslands - Aranguren, Maria Florencia (2023)
Neotropical temperate grasslands comprise the Pampas ecoregion in Argentina. This region is also the center of agricultural development in Argentina, which has led to a significant simplification and homogenization of the landscape. The Tandilia Mountains, located in the Southeast of the ecoregion, house one of the last remnants of the highland grassland that acts as a refuge for several native spe-cies, including both endemic and threatened species. This work aims to present an updated inventory of mammal species that inhabit the highland grassland remnants of the Tandilia Mountains. We used several sources of information to compile the list, including museum collections, citizen science pro-jects (i.e., iNaturalist, EcoRegistros, and Argentinian Network for Monitoring Run Over Fauna), litera-ture, and personal observations. We recorded 40 species of mammals, which include 32 native species and eight exotic species. The richest orders were Rodentia (42.5%), Chiroptera (17.5%), and Carnivora (12.2%). The native mammals found in the Tandilia Mountains represent 44% of the mammal diversity of the Pampas ecoregion, among which there are endemic species of the ecoregion, species whose populations are declining globally, and threatened species. Unfortunately, the presence of protected areas in the system is limited to a few small ones, which highlights the urgency of increasing the number and variety of protected areas. The information presented in this work contributes to the knowledge of biodiversity and the planning of conservation actions for the last remnants of highland grasslands.